2018
DOI: 10.1515/rebs-2018-0065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Safta on Capital Market Integration of South Asia: Evidence from Cointegration Analysis

Abstract: Regional Trade agreements (RTAs) are increasing worldwide because of associated economic benefits such as increased cross border investment and trade, development and integration markets. This paper investigates how South Asian Free TradeAgreement (SAFTA) impact on the integration of South Asian capital markets. Weekly data of capital market indices of three countries (India, Pakistan and Sri Lanka) have been analyzed for overall (1998-2017) and two sub periods, 1998-2006 (Pre SAFTA) and 2009-2017. Correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…China is a big economy and many countries depend on China due to many reasons. Under these projects, there will be a huge network of roads and railways which can help Pakistan’s local industry to have deep connections with China [ 5 , 40 , 41 ]. It’s not only about trade relations, under these projects many students can go to China for higher study and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…China is a big economy and many countries depend on China due to many reasons. Under these projects, there will be a huge network of roads and railways which can help Pakistan’s local industry to have deep connections with China [ 5 , 40 , 41 ]. It’s not only about trade relations, under these projects many students can go to China for higher study and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a worry on a global scale, the implications of human-caused climate change vary depending on the location, system, family, and community. Because of this, the susceptibility of each object varies ( Adger and Kelly, 1999 ; Adger et al, 2004 , 2006 ; Zahid and Khurshid, 2018 ; Zahid et al, 2022a , b ). This has led some researchers to advocate using local assessments to gauge a region’s vulnerability to climate change ( Deressa et al, 2009 ; Below et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, the susceptibility of each object varies (Adger and Kelly, 1999;10.3389/fpls.2022.990785 FIGURE 1 Research model. Adger et al, 2004Adger et al, , 2006Zahid and Khurshid, 2018;Zahid et al, 2022a,b). This has led some researchers to advocate using local assessments to gauge a region's vulnerability to climate change (Deressa et al, 2009;Below et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature has discussed the volatility spillover from energy consumption to stock markets in developed and developing countries [8][9][10][11][12][13][14]. e primary study in this regard was stepped by Hamilton [15] by focused on the impact of oil prices on the economy of the U.S. and found that sharp fluctuation in oil prices has a significant impact on the economy.…”
Section: Introductionmentioning
confidence: 99%